2020
DOI: 10.1111/jam.14612
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary sodium butyrate supplementation on the growth performance, carcass traits and intestinal microbiota of growing‐finishing pigs

Abstract: Aim This study was carried out to investigate the effects of dietary sodium butyrate supplementation on growth performance, carcass traits and intestinal of growing‐finishing pigs. Methods and Results Thirty pigs (27·4 ± 0·4 kg) were randomly assigned to receive one of three diets: basal diet (negative control group), basal diet + 40 ppm zinc bacitracin (positive control group) and basal diet + 0·2% sodium butyrate (sodium butyrate group), respectively. The experiment lasted for 69 days, including 3 days for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
4
15
0
Order By: Relevance
“…It is interesting to note that the high alpha diversity values observed for both groups in our study were similar to those found in sows [1], suggesting an adult and therefore more stable microbiota composition [44], which would likely preclude finding major overall differences in biodiversity. Although in one previous study it was found a reduction of the microbiota diversity after sodium butyrate supplementation, it may have been related to the use of a reduced dose of two antibiotics, colistin and kitasamycin, along with the organic acid [40], as both antibiotics likely had some impact on specific microbial populations [41].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It is interesting to note that the high alpha diversity values observed for both groups in our study were similar to those found in sows [1], suggesting an adult and therefore more stable microbiota composition [44], which would likely preclude finding major overall differences in biodiversity. Although in one previous study it was found a reduction of the microbiota diversity after sodium butyrate supplementation, it may have been related to the use of a reduced dose of two antibiotics, colistin and kitasamycin, along with the organic acid [40], as both antibiotics likely had some impact on specific microbial populations [41].…”
Section: Discussionmentioning
confidence: 86%
“…Most studies focused on the impact that the use of PSB may have on the pig gut microbiota have been usually performed on young piglets (mostly from birth to postweaning) treated for a short period of time [36][37][38][39]. There is only a single recent study on the effect of dietary sodium butyrate in a population of growing-finishing pigs, after being treated for a long period (69 days) [40]. However, in contrast to our study, the samples were collected from the caecum.…”
Section: Discussionmentioning
confidence: 99%
“…The coating of prebiotics or SCFA may be necessary to reach the targeted gut site. Supplementing pig diets with (coated) butyrate has already been used as an efficient strategy to enhance epithelial morphology, homeostasis, and microbiota balance post-weaning [93,94], and has been related to improved growth performance, carcass composition and FE in growing pigs [95]. As pigs of lower FE seem to have a greater response to immune stimuli, increasing the concentrations of anti-inflammatory SCFA (e.g., propionate and butyrate) in the gut may help to moderate an 'over shooting' immune response towards intestinal immune stimuli of the commensal microbiota (e.g., LPS).…”
Section: Applying Knowledge On Fe-and Growth-associated Microbiota To Improve Production Traits In Pigsmentioning
confidence: 99%
“…It is obvious that, although many studies have investigated the effect of antimicrobials on the pig intestinal microbiota, there is no consensus. Considering the same antimicrobials, differences in specific taxa can be observed; e.g., the relative abundance of phylum Bacteroidetes and the lactic acid bacterial genera Lactobacillus and Streptococcus, as well as Coprococcus, has been reported to be both increased and reduced following in-feed antibiotic administration according to the doses, the intestinal segment investigated and the timing of the sampling [147,149,[153][154][155]. Nonetheless, the resilience of the pig gut microbiota and of the dominant taxa to long-term changes due to the administration of antimicrobials is apparent [153,156].…”
Section: Antimicrobialsmentioning
confidence: 99%